MANAJEMEN LANGIT (CELESTIAL MANAGEMENT) SEBAGAI PENDEKATAN SPIRITUAL DALAM PRAKTIK BISNIS - Siti Hidayah (LPPM STIE DHARMAPUTRA SEMARANG, 2010)
AbstractAt this ke-21 century, business life, in this case the emulation in business sector increasingly sharply, so that every practice of business which wish to win the emulation, must have certain competitive advantage compared to the competitors. Competitive advantage of company organization can be formed through various means. One of ways to have the competitive advantage is by applying ethics values and spirituality (celestial values/celestial management) in practice of business. The values are values referring to principle 3 W, namely Worship, Wealth, and Warfare. Keywords: celestial management, spiritual approach, practice of business